2012
DOI: 10.1089/g4h.2012.0010
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotions Associated with “Counter-Strike” Game Playing

Abstract: The overall results are consistent with the hypothesis that predominantly positive emotional reactions are elicited from playing the CS game and concur with positive subjective ratings of happiness. Future studies may explore the relationship of game pleasure and obsessive game play.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Furthermore, studies have shown that ad hoc video games could help adults with anxiety better handle emotional and physiological responses to stressors [78] and improve behavioral performance on anxiety-related stress tasks [79]. Interestingly, in addition to custom-made video games, commercial off-the-shelf (COTS) video games have also shown potential application for improving mental health [19], including the reduction of stress and anxiety (eg, [80][81][82]).…”
Section: Commercial Off-the-shelf Video Games For Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies have shown that ad hoc video games could help adults with anxiety better handle emotional and physiological responses to stressors [78] and improve behavioral performance on anxiety-related stress tasks [79]. Interestingly, in addition to custom-made video games, commercial off-the-shelf (COTS) video games have also shown potential application for improving mental health [19], including the reduction of stress and anxiety (eg, [80][81][82]).…”
Section: Commercial Off-the-shelf Video Games For Relaxationmentioning
confidence: 99%
“…Quantitative nonrandomized studies (n=8) 1 ( 13 None of the 8 studies that used a quantitative nonrandomized methodology accounted for confounders in the design and analysis. Two of these studies did not clearly describe the target population and the sample (inclusion and exclusion criteria) [80,116]. One study did not adopt appropriate measurements and did not report complete outcome data [116].…”
Section: Quality Assessment Outcomesmentioning
confidence: 99%
“…For example, in a study investigating event-specific emotional responses while playing Super Monkey Ball 2 (SEGA)-a platform game (ie, a subgenre of an action game) where the player controls a character who has to jump and climb between suspended platforms while avoiding obstacles-players who experienced not only positive events (eg, acquiring in-game goods) but also some negative events (eg, falling over the edge of the game board) were reported to elicit positively valenced arousal [26]. In another study, predominantly positive emotions were reported while playing the action game Counter-Strike (Valve Corporation), as assessed by an electroencephalogram (EEG) alpha index; in addition, subjective ratings of emotional responses indicated happiness, both during and after the game [37]. Furthermore, dopamine, a neurotransmitter linked to sensations of pleasure and reward, has been detected using positron emission tomography (PET) during video game playing [38].…”
Section: Virtual Reality Video Games Positive Emotions and Relaxationmentioning
confidence: 99%
“…Several studies have shown that computer games played on desktop display devices can generate positive emotions, such as joy or happiness (eg, [35][36][37]). For example, in a study investigating event-specific emotional responses while playing Super Monkey Ball 2 (SEGA)-a platform game (ie, a subgenre of an action game) where the player controls a character who has to jump and climb between suspended platforms while avoiding obstacles-players who experienced not only positive events (eg, acquiring in-game goods) but also some negative events (eg, falling over the edge of the game board) were reported to elicit positively valenced arousal [26].…”
Section: Virtual Reality Video Games Positive Emotions and Relaxationmentioning
confidence: 99%
“…Although the emotions elicited by gaming situations might seem intuitive, studies on the emotional experience of playing first-person shooter games show its complexity. For instance, wounding and killing an opponent causes an increase of positive emotions that could result from the game's progress [15] but also leads to an increase of negative emotions like fear and anger that could result from shooting the rivals [16]. Similarly, wounding or killing one's character (a negative event in the game) leads to positive emotions that could result from alleviating the stress associated with playing [1], but also leads to negative emotions that could result from the game's failure [15].…”
Section: Introductionmentioning
confidence: 99%